Patterns of Pathomorphological Changes in Acute Necrotizing Pancreatitis - I. Kovalska; O. Dronov; S. Zemskov; E. Deneka; M. Zemskova (International Journal of Inflammation)
Acinar necrosis is the basic microscopic sign of acute necrotizing pancreatitis (ANP). Microcirculation disorder is one of the major factors in the pathogenesis and morphogenesis of ANP besides free radicals and damage of enzymatic origin. This study is dedicated to the description of microscopic changes in the pancreatic stroma in ANP, which leads to destruction of the exocrine pancreas with a putative mechanism of endocrine function preservation. This study has been carried out on histological samples of pancreas from 224 patients with ANP. Histological staining was performed with hematoxylin-eosin (H&E), Masson, Gomori methods, and PAS. Microscopy was performed with magnifications of 40×, 100×, and 400×. Vascular endothelial desquamation, stasis, and sludge are typical changes in microcirculation observed in early stages of ANP. Initially, parietal circular intravascular microthrombosis accompanied by endothelial desquamation as early as stromal swelling occurs with no detectable necrosis. Residual stroma appears between areas of necrosis and intact pancreatic tissue. Mucoid swelling is first seen in the perivascular spaces extending to the parenchyma and changing into fibrinoid imbibition causing further necrosis. Reticulin argyrophilic backbone surrounding the pancreatic acini and small ducts decompose. Pancreatic structures, which may be preserved in necrotic tissue, include nerves, major ducts, and Langerhans islets.